Standard concentration infusions in paediatric intensive care: the clinical approach. (14th August 2016) - Perkins, Joanne; Aguado‐Lorenzo, Virginia; Arenas‐Lopez, Sara
Abstract: The use of standard concentrations of intravenous infusions has been advocated by international organisations to increase intravenous medication safety in paediatric and neonatal critical care. However, there is no guidance on how to identify and implement these infusions leading to great interunit variability. Objective: To identify the most appropriate clinical concentrations required by our paediatric intensive care unit (PICU) population with regard to accuracy of delivery and overall fluid allowance. Methods: Firstly a matrix was used to balance the concentration, dose and infusion volume (weight range 1.5–50 kg). Results were further refined considering: patient fluid allowance based on fluid volume targets, infusion pump accuracy and challenging each infusion against clinical scenarios requiring administration of multiple drug infusions found in PICU. Consideration was given to the standard concentrations routinely used in adults, in order to assess whether alignment with paediatrics was possible for some of the concentrations proposed. Finally a risk assessment of the infusions was conducted using the NPSA 20 tool. Key findings: Twenty‐five drugs identified as the most commonly used intravenous infusions in the unit. For the majority of the medicines, three weight bands of standard concentrations were necessary to cover the children's weight ranges and kept within predefined fluid requirements and accuracy of delivery. Conclusions: This work shows a patient focused systematic approach for defining and evaluating standardised concentrations in intensive care children.